1995
DOI: 10.1038/ng0595-104
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of the Huntington's disease protein and discrimination of the normal and mutated form

Abstract: Huntington's disease (HD) results from the expansion of a polyglutamine encoding CAG repeat in a gene of unknown function. The wide expression of this transcript does not correlate with the pattern of neuropathology in HD. To study the HD gene product (huntingtin), we have developed monoclonal antibodies raised against four different regions of the protein. On western blots, these monoclonals detect the approximately 350 kD huntingtin protein in various human cell lines and in neural and non-neural rodent tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
224
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(239 citation statements)
references
References 38 publications
14
224
0
1
Order By: Relevance
“…51 Other studies have also concluded that both Huntingtin and HAP1 have a function in vesicular trafficking. [52][53][54] Of note is the fact that psychotic symptoms sometimes leading to a diagnosis of schizophrenia are found in Huntington's disease patients. 55,56 BBS4 and TTC8 are two members of the BBS family of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…51 Other studies have also concluded that both Huntingtin and HAP1 have a function in vesicular trafficking. [52][53][54] Of note is the fact that psychotic symptoms sometimes leading to a diagnosis of schizophrenia are found in Huntington's disease patients. 55,56 BBS4 and TTC8 are two members of the BBS family of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Huntingtin is present in the cytoplasm, but not the nucleus or mitochondria of most cell types tested so far (Strong et al 1993 ;DiFiglia et al 1995 ;Gutekunst et al 1995 ;Trottier et al 1995 ;Wood et al 1996). The normal cellular function of this cytoplasmic protein remains unclear although an association with components of the cytoskeleton and synaptic vesicles in presynaptic nerve terminals suggest a role in intracellular transport (DiFiglia et al 1995 ;Gutekunst et al 1995).…”
Section:     '  mentioning
confidence: 99%
“…Huntingtin has been immunolocalized in a series of studies that have shown a strong cytoplasmic immunoreactivity (Trottier et al 1995;DiFiglia et al 1995;Gutekunst et al 1995;Sapp et al 1997), although there have been reports of nuclear localization (De Rooij et al 1996). However, the intranuclear inclusions have shown immunoreactivity associated only with epitopes in the furthermost N-teminal regions of huntingtin, the region within which the polyglutamine sequence resides Becher et al 1998).…”
Section: Introductionmentioning
confidence: 99%